Adoption of Retail Internet Banking: A Study of Demographic Factors - Jayaraman, Munusamy; Ernest Cyril, de Run; Shankar, Chelliah; Sanmugam, Annamalah (Journal of Internet Banking and Commerce, 2013)
This study focuses on the adoption of retail internet banking among consumers in the Klang Valley, Malaysia and the impact of demographics factors on such adoption behavior. This study adopts a quantitative approach using surveys conducted at banks. The results indicate that while the hypotheses pertaining to gender, race, income, educational level and occupation were not supported but age is supported. Therefore, the current research indicates that the age of retail banking consumers affects the adoption of internet banking among Malaysian consumers. The result also suggests that consumers in the age group below 25 years old are the major contributor to the differences. Based on these findings, we conclude that younger consumers are more likely to adopt internet banking. Therefore, the result suggests implications for retail bankers in Malaysia to adopt appropriate strategies to encourage retail internet banking for other age categories of consumers in Klang Valley. By doing so, it enables the banks in Malaysia to save costs of maintaining physical distribution systems through providing bigger scale of Internet retail banking services.